The Stability Constants and Thermodynamic Parameters of Borate - Carbohydrate Complexes by pH Measurements (Journal of the Bangladesh Chemical Society, 2012)
The complexation of borate with carbohydrates was studied potentiometrically at  temperatures 298.15-328.15K in aqueous medium at constant ionic strength, I = 0.1M  KCl. The stability constants (?) and thermodynamic parameters of borate-carbohydrate  complexes were determined using the technique proposed by Verchere and Hlaibi.  Carbohydrates such as D-fructose, D-Sorbitol, D-Mannitol, D-Galactose, D-Glucose and  D-Raffinose were used as ligands in this study. The ?1 values for the complexes at  different temperatures were found to follow the order: D-fructose > D-Sorbitol > DMannitol > D-Galactose > D-Glucose > D-Raffinose. The ?G0 values were found to be  negative and the negative values increased according to the above order. The values of  ?H0 and ?S0 were both negative which indicated that the complex formation was an  exothermic process and the spontaneity of its formation is driven by enthalpic  contribution overcoming the negative contribution of ?S0. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11766 Journal of Bangladesh Chemical Society, Vol. 25(1), 15-20, 2012